2021
DOI: 10.3389/fpsyg.2021.727013
|View full text |Cite
|
Sign up to set email alerts
|

Service User Experiences of How Flexible Assertive Community Treatment May Support or Inhibit Citizenship: A Qualitative Study

Abstract: The aim of this study was to explore and describe service user experiences of how receiving services from a Flexible Assertive Community Treatment (FACT) team may support or inhibit citizenship. Within a participatory design, individual interviews with 32 service users from five Norwegian FACT teams were analyzed using thematic, cross-sectional analysis. The findings showed that FACT may support citizenship by relating to service users as whole people, facilitating empowerment and involvement, and providing pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…This emphasizes the importance of collaboration in both urban and rural FACT teams, implying the need to increase the focus on service system collaboration in the FACT model. However, a study of patients of urban and rural FACT teams reported that the patients experienced FACT to be better than their earlier treatment because the FACT teams to a large extent provided the services they needed ( 73 ). Nevertheless, one challenge that remains is the remoteness in relation to crisis management.…”
Section: Discussionmentioning
confidence: 99%
“…This emphasizes the importance of collaboration in both urban and rural FACT teams, implying the need to increase the focus on service system collaboration in the FACT model. However, a study of patients of urban and rural FACT teams reported that the patients experienced FACT to be better than their earlier treatment because the FACT teams to a large extent provided the services they needed ( 73 ). Nevertheless, one challenge that remains is the remoteness in relation to crisis management.…”
Section: Discussionmentioning
confidence: 99%
“…Norwegian FACT teams have been described by other service providers as working to promote collaboration and improving collaboration in the service system [ 61 ]. However, a study that interviewed patients from the same study as ours noted the potential for improvement in their collaboration with other services [ 77 ]. Our findings indicate that collaboration is essential for FACT teams in complex and fragmented systems.…”
Section: Discussionmentioning
confidence: 99%
“…This way of working may promote the opportunities for integration. The previously mentioned study that interviewed patients from the same FACT teams as our described that being treated as a whole person and finding help with all their challenges from the same team made them feel safer, improved their daily life situation and made it easier to relate to the service system [ 77 ]. This indicates that FACT teams can contribute to better integrated care even in complex and fragmented service systems.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these patients may benefit from a more customized, flexible setup with faster turnaround and better availability [ 7 ], such as the Flexible Assertive Community Treatment model (FACT). FACT provides prolonged, extensive, and combined services to persons with severe substance use or mental disorders [ 44 ]. Such a low-threshold service is resource demanding but could prove a cost-effective option from a longer-term socioeconomic perspective, at least for some SUD patients.…”
Section: Discussionmentioning
confidence: 99%